2021
DOI: 10.3390/agriculture11080721
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Efficiency Determined by the 15N Dilution Technique in Maize Followed or Not by a Cover Crop in Mediterranean Chile

Abstract: Nitrogen (N) in a maize crop is a determining yield factor, but its negative impact on the environment is also known. Therefore, it is necessary to propose mitigation strategies that allow an improvement in the N fertilizer efficiency (NFE), such as the use of cover crops (CC) and the adjustment of the fertilizer dose. The objective of the study was to determine NFE using 15N isotopic techniques and nitrate (NO3−) leaching in a maize–fallow versus a maize–CC rotation with optimal and excessive doses of N in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Recently, many studies have focused on δ 15 N abundance in the optimization of nitrogen fertilizer use [31][32][33]. Using fertilizers labelled with 15 N isotope made it possible to determine crop use efficiency and the optimal application of fertilizer, which will greatly enhance the sustainability of the agroecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have focused on δ 15 N abundance in the optimization of nitrogen fertilizer use [31][32][33]. Using fertilizers labelled with 15 N isotope made it possible to determine crop use efficiency and the optimal application of fertilizer, which will greatly enhance the sustainability of the agroecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to our findings, other studies have shown neutral effects on N uptake by maize in cover crop rotation systems. Salazar et al (2021) did not observed effect of cover crops on N content in maize compartments when compared to fallow. These results can be explained by the possible lack of synchrony of cover crops residue N release and maize N demand .…”
Section: Effect Of Cover Crop Rotation Systems On N Uptake By Maizementioning
confidence: 60%
“…However, the N fertilizer use efficiency can decrease if the N rate was excessive, contributing to losses of N and environmental issues (Salazar et al, 2021), and must be avoided in agricultural systems.…”
Section: N Accumulated In Maize Compartmentsmentioning
confidence: 99%
See 2 more Smart Citations